DESCRIPTIVE STUDY ABOUT PSYCHOLOGICAL CAPITAL FOR THE SALES OFFICE HEAD AT PT. ASTRA INTERNATIONAL TBK – HONDA SALES OPERATION - Puji Tania; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2017)
Sales Office Head (SOH) at PT. Astra International.Tbk. - Honda Sales Operation (HSO) has a huge amount of workload that demand them to be independent. As the result, they’re giving up easily and have a high tendency to resign. This will bring a bad impact for the company as SOH turnover become more frequent. The concept of psychological capital (Psycap) approach is assumedly quite suitable to be used in managing human resources in HSO, especially SOH. Psycap is an approach on positive potential that consists of hope, efficacy, resilience, and optimism that will enable SOH to work optimally, even in a tough situation. Research is conducted on SOH in Honda HSO by using positive psycap approach that aims to obtain an overview of SOH psycap at HSO. The study is descriptive and applied research with a quantitative method using convenience sampling technique. Instrument used in this study is psychological capital questionnaire, distributed throughout the 68 SOH respondents. The result indicates that psychological capital of SOH in HSO is at high levels. In accordance with the conditions of SOH’s work, the dimensions that need further development the most are the dimension of optimism and resilience.